2018
DOI: 10.1091/mbc.e17-11-0693
|View full text |Cite
|
Sign up to set email alerts
|

Targeted protein unfolding uncovers a Golgi-specific transcriptional stress response

Abstract: In eukaryotic cells, organelle-specific stress-response mechanisms are vital for maintaining cellular homeostasis. The Golgi apparatus, an essential organelle of the secretory system, is the major site of protein modification and sorting within a cell and functions as a platform for spatially regulated signaling. Golgi homeostasis mechanisms that regulate organelle structure and ensure precise processing and localization of protein substrates remain poorly understood. Using a chemical biology strategy to induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 62 publications
2
29
0
Order By: Relevance
“…In contrast, we showed that Herp deficiency did not have any impact on CREB3 stability, although the Herp protein was dramatically upregulated in SEL1L-deficient cells even under resting conditions. Recently, microarray analysis using cells treated with putative Golgi stress-inducing reagents revealed a variety of candidate genes associated with protein transport, glycosylation and Golgi homeostasis [16,17,27,34]. The ERAD machinery is composed of a well-coordinated protein complex including SEL1L, Herp, Hrd1, Derlin, osteosarcoma amplified 9 and GRP78 [19-23]; however, Herp knockout mice were born and grew normally [30] despite the fact that conditional SEL1L knockout mice decreased in body weight and died within 2-3 weeks [25].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, we showed that Herp deficiency did not have any impact on CREB3 stability, although the Herp protein was dramatically upregulated in SEL1L-deficient cells even under resting conditions. Recently, microarray analysis using cells treated with putative Golgi stress-inducing reagents revealed a variety of candidate genes associated with protein transport, glycosylation and Golgi homeostasis [16,17,27,34]. The ERAD machinery is composed of a well-coordinated protein complex including SEL1L, Herp, Hrd1, Derlin, osteosarcoma amplified 9 and GRP78 [19-23]; however, Herp knockout mice were born and grew normally [30] despite the fact that conditional SEL1L knockout mice decreased in body weight and died within 2-3 weeks [25].…”
Section: Resultsmentioning
confidence: 99%
“…Considering these findings, canonical ER stress pathways and noncanonical ER-resident CREB3 family members are activated by distinct cellular dysfunctions, as observed in this study, but their downstream targets might partially overlap. Recently, microarray analysis using cells treated with putative Golgi stress-inducing reagents revealed a variety of candidate genes associated with protein transport, glycosylation and Golgi homeostasis [16,17,27,34]. Therefore, an elaborate comparative analysis of their promoter sequences might uncover the conserved sequences specifically recognized by members of the CREB3 family and clarify the whole picture of the Golgi stress response.…”
Section: Resultsmentioning
confidence: 99%
“…The Golgi apparatus has been suggested as a sensor of stress and regulator of cell death processes 9 . A Golgi-stress response has been described in several systems depicting transcriptional changes in expression of the chaperone HSP47, transcription factors such as TFE3 and ETS whose target genes are related to spliceosome function and cell death induction, as well as Golgi structural genes such as GCP60 34,36,37,[58][59][60][61] . Yet, the underlying mechanisms responsible for controlling Golgi morphology in response to stress remain poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…A Golgi quality control mechanism has been described as a distal checkpoint to sort aberrant proteins following exit from the ER [70][71][72][73][74] . A recent study by Crews and colleagues directly identified a protein misfolding response at the Golgi 58 . In yeast, misfolded or damaged proteins at the Golgi were shown to undergo ubiquitination by the DSC/Tul1 E3 ligase complex, which targets them to vacuolar degradation 70,75,76 .…”
Section: Discussionmentioning
confidence: 99%
“…Over the past 10–15 years there have been an increasing number of studies reporting perturbations in the structure of the Golgi ribbon associated with diseases, disorders and infections. These include stress responses , metabolic perturbations , cancer , neurodegeneration and various infections such Chlamydia which remodel the Golgi membranes . Many of the alterations in Golgi structure involve the scaffolds discussed in this review which influence the microtubule and actin networks.…”
Section: Changes In Golgi Structure In Diseasementioning
confidence: 99%